Interdependence among Capital Markets of Germany, Poland and Baltic States - Tomas Meluzin; Marek Zinecker; Michal Bernard Pietrzak; Marcin Faldzinski; Adam P. Balcerzak (Institute of Economic Research (IER), 2016)
The growing interdependencies among capital markets are becoming significant factor affecting process of risk management both at macro and microeconomic level. Thus, the aim of the article is the analysis of interdependencies among capital markets of Germany, Poland and Baltic States. In order to measure the interdependencies DCC-GARCH model was applied. The research was conducted for the years 2004-2015. The capital market of Germany was taken as the one that has the biggest influence on the analysed Central and Eastern European markets. The conducted research enabled to determine the different nature of the interdependencies among the capital markets of Baltic States and Poland on one side and German capital market on the other side.
Keywords: G15; C58; 330; capital market; conditional variance; conditional correlation; DCC-GARCH model; integration